Learner Participation in Science Learning: Creating a Humanized Science Classroom - Thapaliya, Pratima (Educational Journal, 2023)
As science learners, learners can learn science from their enriched cultural life world. However, the disempowering forces embedded in science pedagogical practices demotivate the learners to participate in the active science learning process. In this context, this research addresses the question: How have I explored learner participation in science learning to create a humanized science classroom? I applied auto ethnography as a research method and inquiry to portray the critical reflexive narratives I experienced in my science learning journey. The research shows that the learners’ participation in science learning is in/directly influenced by the in/formal modes of science learning. The rigorous and unjust formal schooling cultures demotivate the learners to participate in science learning autonomously. The science teachers must know the learners’ lived experiences and cultural worlds by creating a dialogic space between teachers and students. It can also support modifying and cultivating their internal selves through individual and collective participation. Therefore, the research also offers to know and value the learners’ creativity and acknowledge the learners’ learning experiences beyond the formal academic settings. Furthermore, science teachers need to view the learners through humanized lenses to motivate learners for their autonomous participation in science learning. It possibly counteracts the rigorous schooling cultures that emphasize the directed participation of learners and transform their dogmatic identities.